Synthesis and antimicrobial evaluation of some new pyrazole, pyrazoline and chromeno[3,4-c]pyrazole derivatives - Abunada,Nada M. (2009)
Some new pyrazole-5-carbonitrile derivatives 8, 9 and pyrazole-5-carboxamide 13 were synthesized by the cycloaddition reaction of nitrilimines 3, 4 to α-cyanocinnamonitriles 5a-f and α-cyanocinnamamide 12a, b respectively. On the other hand 3, 4 add to ethyl α-cyanocinnamate 14a-f to give ethyl 2-pyrazoline-5-carboxylate derivatives 15, 16. Also, cycloaddition of 3, 4 to 3-cyanocoumarin 19a or 3-phenylsulphonylcoumarin 19b or 3-bromocoumarin 19c give chromeno[3,4-c]pyrazol-4(3H)-one derivatives 20. In the same direction, the cycloaddition of 3, 4 to 3-acetylcoumarin 22 and 3-benzoylcoumarin 23 gives the corresponding dihydrochromeno[3,4-] pyrazol-4(3H)-one 24 and 25 respectively. Oxidation of 24 and 25 give 20. Most of the prepared compounds showed good to moderate antibacterial and antifungal activities.